Recent Advances in the Synthesis of Sulfonamides Intermediates - Liu, Wei; Chen, Jianli; Su, Weike (Pharmaceutical Fronts, 2024)
Sulfonamides are one of the most important synthons in drug synthesis, which can increase the water solubility of drugs and regulate their metabolism in vivo. According to statistics, nearly 30% of sulfur-containing drugs on the market contain sulfonamide groups, including omeprazole, hydrochlorothiazide, and other best-selling drugs. Synthesis of sulfonamide is therefore a very important part of new drug development and active pharmaceutical ingredient manufacturing. In this review, we will focus on the recent 5-year advances in the field of synthetic research and structural modification of sulfonamide-containing drugs and their intermediates. The synthesis strategies, including S−N construction, C−N cross-coupling, N−H functionalization, and C−H sulfonamidation, are discussed, hoping to provide new ideas for the researchers to prepare sulfonamides in a green and efficient way.
Keywords: sulfonamides; S−N bond formation; C−N cross-coupling; N−H functionalization; C−H amination